A multi criteria group decision making approach for collaborative software selection problem - Kara, Selin Soner; Cheikhrouhou, Naoufel (IOS PRESS, 2014)
Today, operational managers are experiencing difficulties in selecting the software that best suits their increasing number of requirements. These decision makers need to clarify what their needs are, what these packages offer and which software packages best fit their needs. Among the available tools, collaborative software is used to manage teams of people and different types of communication resources. This paper proposes a multi-criteria decision making technique for the selection of collaborative software. The technique is applied to a software company that develops business management solutions for Small and Medium sized Enterprises. The proposed group decision-making methodology is designed to handle both quantitative and qualitative criteria. Criteria weights are calculated using a two-step multi-criteria decision making method: Fuzzy Analytical Hierarchy Process for the experts' and criteria weights, and Technique for Order Preference by Similarity to Ideal Solution for ranking the alternatives. Results show that the presented methodology reduces the uncertainty in decision-making and provides robust solutions.
Keywords: Collaborative software; fuzzy AHP; group decision making; TOPSIS; FUZZY MCDM APPROACH; SYSTEM SELECTION; AHP; Computer Science